ЛИЗАРДИТ И САПОНИТ В КИМБЕРЛИТОВОЙ ТРУБКЕ КАТОКА (ЗАПАДНАЯ АФРИКА) - Зинчук Н.Н.; Жухлистов А.П.; Котельников Д.Д.; Б стегницкий Ю.Б. (My University, 2006)
An unusual association of simple (1T, 3R) and two complex (nonstandard) orthogonal polytypes of lizardite was found, for the first time, within porphyry kimberlites occurring in volcanogenic-sedimentary rocks. One of the nonstandard polytypes is characterized by the ordered six-layered structure, with the same orientation of adjacent layers, and another one has a semi-ordered six-layered (three-layered) structure with more complicated, than for simple polytypes, regulation in alternating of the contrary-wise oriented layers.
Keywords: 5491548